Esperanza y satisfacción con la vida: probando los roles mediadores de la autoestima en tres culturas asiáticas - Bernardo, Allan B. I.; Khan, Aqeel; Salanga, María Guadalupe C. (Acción Psicológica, 2018)
The relationship between well-being and the personal strength of hope has been elaborated by the identification of internal (self) and external (family, peers, spiritual) locus-of-hope dimensions. Du, Bernardo, and Yeung (2015) showed that self-esteem (personal and relational) mediates the relationship between locus-of-hope and life satisfaction. Locus-of-hope’s goal-related thoughts involve self-evaluation that may either enhance or diminish self-worth, which then influences life satisfaction. We tested the mediated model in three cultural groups: Malaysians, Macau Chinese, and Filipinos. Participants completed scales measuring locus-of-hope, personal and relational self-esteem, and life satisfaction. Path analysis showed significant indirect effects in all cultures: (a) internal locus-of-hope on life satisfaction, mediated by personal self-esteem, and (b) external-family locus-of-hope on life satisfaction, mediated by relational self-esteem. Other significant indirect effects were found in specific cultural groups. Cross-cultural similarities and differences are discussed with reference to how distinct cultures give different meanings to forms of agency associated with the personal strength of hope, creating distinct pathways towards life satisfaction.